STATE FISCAL SPACE RESEARCH FORMATION IN THE CONTEXT OF SUSTAINABLE DEVELOPMENT - Žubule, Ērika; Puzule, Anita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The scientific objective of the research is to carry out the country's fiscal space for the study of public finance policy affects the context of sustainable development. The selection and topicality of the research issue is justified by the fact that each country's sustainable development is affected by the government's policies. One of its main components is fiscal or budgetary policy. Traditionally, it is defined as the money required for setting revenue and expenditure policy that is needed to ensure the government operation, but the economic interpretation says it is the economy regulation system through taxes and government spending. It is emphasized that it is closely linked with the state's role in the redistribution of society profits, determining the state budget's proportion in the gross domestic product, defining objectives for the common tax burden, budgetary expenditure, allowable deficit, volume, and structure of the government debt. In addition, the concept of “fiscal space” correlating with application of the fiscal policy measures becomes topical. Thus, the government is able to influence income of both the society generally and certain groups of residents, their purchasing power and impact on economic development in general. It defines the need of concept fiscal space.